Intertextualidade camoniana nas crônicas de Carlos Drummond de Andrade - Fiquer, Beatriz Teixeira (2015)
The objective of this thesis is to contribute with intertextuality studies, by examining Carlos Drummond de Andrade´s chronicles in which there is intertextuality with the life and work of Luis Vaz de Camões. Therefore, analyses have been carried out of Drummond´s chronicles published on Jornal do Brazil dated 1980 and 1984 since most of them have not yet been collected in books and neither studied under this research point of view - and the ones mentioned by professor Gilberto Mendonça Teles in his book Camões and Brazilian poetry and the camonian myth in Portuguese Language (2001) in which the author presents statistics of how many times the name Camões and his works appear in Drummond´s texts until the beginning of 1981. The development of this work was based on proposals from Sant Anna (1985); Paulino, Walty, Cury (1995); Piègay-Gros (1996); Koch, Bentes and Calvacante (2008) about studies of intertextuality theories and analysed how the Brazilian writer was influenced by verses of the Portuguese poet, how often and how it has happened. Historical/social context was examined when necessary to understand the texts and the treatment given by Drummond to Camões verses. This way, as a result of reading over seven hundred chronicles, this paper shows the different forms in which intertextuality occurs, mainly the explicit one, analysing how it was used by the Brazilian writer, and showing the existence of Camões presence in Drummond´s texts. It also proves that besides Drummond´s poetry his chronicles has very rich material for further studies